RISK ANALYSIS OF INVESTMENT A NEW FACTORY WITH MONTE CARLO SIMULATION - I Ketut Gunarta (Jurnal Ilmiah Ekonomi Bisnis, 2009)
A case study of an investment in developing a new factory was conductedone of critical factors which are concern in foreign investment evaluation,exchange rate of US$ to IDR (Rupiah). The exchange rate’s fluctuationeffect on the financial engineering project and also the firm performance,investment was funded by export debt. The exchange rate risk wasCarlo simulation model.Key Words: Risk, Monte Carlo Simulation, Financial Indicators.